Socio-economic contribution of cassava varietal improvement to the small farmer communities in Asia - Kawano, Kazuo (International Center for Tropical Agriculture, 1998)
The success or failure of any large-scale crop breeding program should be measured by achievement of the following step-by-step goals: 1) Establishment of a breeding program 2) Building of effective research capability 3) A large number of genotypes produced and evaluated 4) Selection of superior genotypes 5) A large number of cultivars released 6) A considerable area planted with new cultivars 7) Additional yield and quality as a result of the planting of new cultivars 8) Additional economic benefits generated by the adoption of new cultivars 9) The less privileged strata of society receive the greatest share of the profits 10) Beneficial social changes brought about by the planting of new cultivars